Varstvo osebnih podatkov v podjetju: priročnik za mala in srednja podjetja (University of Maribor Press, 2019)
Personal Data Protection in Enterprise: Manual for Small and Medium-sized Enterprises. Human privacy is inviolable. Personal data is a part of the individual’s privacy and therefore the highest legal protection is guaranteed for it. The development of modern technologies and the continuous accumulation of data constitutes a serious threat to the personal data protection, which were easily accessed for various, highly damaging purposes. The European Union legislator has therefore adopted a new regulation on the protection of personal data, which is in force since 28 of May 2018. Its purpose is to enhance the protection of personal data in digital society. The provisions of the regulation are also binding for Slovenian companies and entrepreneurs who must perform privacy policy, in accordance with new rules.